Chinese furniture exploring China's furniture culture - Zhang, Xiaoming 1971- (Cultural China Series, 2016)
Chinese Furniture is an outstanding representative of the Chinese arts. It has the bright feature of oriental arts and is honored as a pearl oriental arts. As for the unique feature of Chinese furniture， some say it completely give full play to the inborn nature of wood and display the beauty of the texture of wood. Some say it has perfect artistic shape. Its lines are delicate，easy and smooth and its structure reasonable and elegant. Some say its producing technique is superb，and mortise precise and decorations elegant. Some say it has long historical grace，elegant artistic style and colorful charm.